The Influence of Works Ethics and Dicipline on Employee Performance on PT. Pawbroker Malalayang of Manado City - Ratag, Ricardo A.; Mumu, Sweetly; Mantur, Mercy (Formosa Journal of Applied Sciences, 2024)
This study has a mission to assess the impact of work ethics and work discipline on the performance of employees of PT Pegadaian Malalayang Branch, Manado City. This study applied quantitative techniques, by applying the Multiple Linear Regression test. The study output indicates that work ethics partly has a positive and insubstantial effect on employee performance, while work discipline is partly able to have a positive and substantial impact on employee performance and together work ethics and discipline are able to have a positive and substantial effect on employee performance of PT Pegadaian Malalayang Branch Manado City. This study is expected to be a benchmark for employees of PT Pegadaian Malalayang Branch, Manado City so that in the future they can further improve their performance at work. These findings can also serve as a reference for further studies in studying the factors that can support the increase in employee performance in a company.